Saving Hidden Paradise: An Analysis of Sustainable Tourism Communication Needs for the Conservation of the Sawarna Beach Ecosystem, Indonesia - IRAWAN, Enjang Pera; BATE, Andi Pajolloi; RISMAHAYADIN, Imam (Journal of Environmental Management and Tourism, 2025)
Tourism is recognized as an important sector for the national economy, with significant contributions to GDP and foreign exchange earnings. This study was conducted under the auspices of Sawarna Beach as a result of increased tourism contributing to the economic growth of the local ecosystem and the general population. This study aims to analyze the communication needs of sustainable tourism that can support the preservation of the Sawarna Beach ecosystem. The method used is a case study with qualitative approach. Data were obtained from observations, study documentation, focus group discussions (FGD), and interviews. Collaboration among various stakeholders in Sawarna Beach, including district government, BUMDes, business owners, NGOs, Lebak Regency government, media, and academics, is crucial for promoting sustainable agriculture and environmental conservation. In addition, each group has specific communication needs, such as discussion forums for district officials, information sheets for tour operators, training programs for tour guides and accommodation owners, as well as storage and information areas for tourists for tour guides. This study also suggests that effective education thru social media and academic materials is crucial for enhancing participation and sustainable environmental maintenance. All of this significantly contributes to the development of stricter and more sustainable tourism practices in ecologically sensitive areas.